In vitro Antibacterial and in silico Evaluation of Ficus benghalensis Methanolic Bark Extract, as Potential Anti-MRSA Agent - Abdulhaq, Ahmed A; Hershan, Almonther Abdullah (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Methicillin-resistant Staphylococcus aureus (MRSA), known to be highly resistant bacterium, leading to dreadful infections with limited treatment options. Objectives: The current study mainly focused to investigate the anti-staphylococcal activity of Ficus benghalensis methanolic bark (FBMB) extract against Methicillin-resistant Staphylococcus aureus (MRSA). Materials and Methods: The assessment of Ficus benghalensis methanolic bark (FBMB) extract was performed by agar well diffusion method and broth dilution method. Further, the pathogenic factors such as formation of biofilm, hemolysis, adhesion and staphyloxanthin production were evaluated to confirm antibiofilm and anti-adhesion activity. Cytoplasmic leakage analysis was also carried out to confirm the antibacterial activity of the extract. Results: From agar well diffusion method, it was observed that even at low dosage (1.6 mg/ml) showed the zone of inhibition which is significantly as dose dependent manner. 50 mg/ml extract showed Minimum inhibitory concentration (MIC) and 100 mg/ml extract showed minimum bactericidal concentration (MBC). The inhibitory activity of extracts was observed information of biofilm, hemolytic activity and production of staphyloxanthin. Oxidative survival resulted in decreased colonies of Methicillin-resistant Staphylococcus aureus (MRSA) and cytoplasmic leakage elevation was observed with the treatment. Further, in silico analysis also confirms the binding and interaction of the active molecules of FBMB extract, such as Beta-sitosterol, Lupeol Acetate and Alpha-amyrin against the MSCRAMMs family of MRSA using AutoDock Vina, Accelrys BIOVIA and pyMol tools and furthermore these molecules have better pharmacokinetic profile as based on Lipinski's rule of five violation. Conclusion: Ficus benghalensis methanolic bark extract, can be used as an drug candidate for antibiotic-resistant infection caused by Methicillin-resistant Staphylococcus aureus (MRSA).
Keywords: MRSA; Ficus benghalensis; Bark extract; Anti-biofilm; Anti-virulence; Anti-bacterial; Membrane stability; in silico